Between spiritual wellbeing and spiritual distress: possible related factors in elderly patients with cancer - Sílvia Caldeira; Emilia Campos de Carvalho; Margarida Vieira (Universidade de São Paulo, 2014)
OBJECTIVE: this article describes the assessment of the spiritual wellbeing of elderly patients with cancer submitted to chemotherapy and possible predictive factors of the spiritual distress diagnosis. METHODOLOGY: this is a methodological study for clinical validation of a nursing diagnosis, using interviews to assist in completing the form. RESULTS: 45 elderly patients participated in this study, Catholics, mostly female, diagnosed with breast cancer, average age of 70.3 years. The prevalence of spiritual distress was of 42%; 24.4% of the elderly patients were under anti-depressant medication. A significant association was noted between spiritual distress, anti-depressant medication and level of education; an increase (not significant) was acknowledged at the start of the treatment. CONCLUSION: these results emphasize the relevance of clarifying this diagnosis and the responsibility of nurses to provide spiritual care to patients. Interventions should be planned appropriately every time a nursing diagnosis is identified as a complex answer and for which pharmacological treatment is not sufficient.